Reservoir Characteristics and Its Comprehensive Evaluation of Gray Relational Analysis on the Western Sulige Gas Field, Ordos Basin, China - Xinping Liang; Qingbin Xie; Mingyu He; Quanyou Liu; Vladimir Morozov (Geofluids)
Although the Sulige gas field has been developed for several years, accurate reservoir classification, evaluation, and prediction is still a worth-exploring scientific issue as this is a necessary procedure which could give the guidance of well deployment during later gas field development. Here, based on the analysis of lithological features and diagenesis, we give an evaluation of gas reservoirs in the western Sulige gas field by using the improved method of gray relational analysis. Our results show that the study area Su-54 block is dominated by low permeability and low porosity litharenite and lithic silicarenite with clear evidence of strong diagenesis processes. Compaction is believed to be relatively strong due to the great burial depth and destroy most of the primary pores. Based on the premise of a lower limit of an effective reservoir, we select five parameters (permeability (K), porosity (Φ), effective sand thickness (M), effective sand/sand thickness ratio (D), and gas saturation (Sg)) to calculate the correlation coefficient, relational degree, and index weights for reservoir quality evaluation. By weighted gray correlation theory, the dynamic testing data—effective thickness of gas production data—is used as mother sequences. The results show that the predicted favorable areas for gas exploration and development coincide well with sedimentary and sand body distribution (e.g., point bars and central bars) in the study block; well blocks such as s372, s373, s374, and e24 could be future key development targets. This also indicates a broader application of the gray relational analysis to quality evaluation and distribution prediction of reservoirs. Therefore, our findings could give a new theoretical and practical guidance for the later gas exploration and development, for the search of hidden stratigraphic lithological traps, and for the improvement of the proven rate of oil and gas resources in this area.